Noradrenergic-dependent functions are associated with age-related locus coeruleus signal intensity differences - Kathy Y. Liu (Nature Portfolio, 2020)
Alterations of locus coeruleus signal intensity have been associated with functional changes in health and disease. Here, the authors tested a pre-registered hypothesis on a large number of subjects as part of the Cam-CAN consortium.